DAMPAK PROGRAM KARAKTER ISLAMI PADA KARAKTER ANAK USIA DINI - Jadid, Khalis (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
This study aims to determine the impact of the Islamic character program at Bunda Medan Satria Kindergarten Bekasi and its supporting and inhibiting factors. This study is a qualitative study, and data were collected through interviews, observations, and documentation. Interviews involved the principal, teachers, and student guardians, while observations focused on Islamic character program activities and student behavior. Documentation collected supporting data in the field. The results show that the Islamic character program is an important part of Bunda Kindergarten, including the integration of Islamic values in learning, teaching the Qur'an, Hadith, worship, ethics, and Islamic habits. The program has a positive impact on children's character, such as the habit of reading prayers, surahs, hadiths, as well as worship practices, such as prayer, fasting, and almsgiving. Supporting factors are Islamic extracurricular activities (tahsin and tahfidz), then diverse learning media, social environment, and competent educators. Obstacles include lack of parental support, differences in family background, and children's character.